Reading Historical Fiction - Mitchell, Kate. author. aut Link
XII, 243 p.
Keywords: This collection examines the intersection of historical recollection, strategies of representation, and reading practices in historical fiction from the eighteenth century to today. In shifting focus to the agency of the reader and taking a long historical view, the collection brings a new perspective to the field of historical representation.